2018
DOI: 10.29328/journal.jsmt.1001020
|View full text |Cite
|
Sign up to set email alerts
|

Progresses of the Badminton equipment relate to exercise: Some training aspects

Abstract: Background: With the development of sports science and badminton equipment, the roles of badminton shoes, such as to alter lower-extremity biomechanical parameters, prevent sports injuries and enhance performance, were confi rmed by a mass of studies. Methods: In this study, a serial of methods including literature review, visualization analysis, mathematical statistics, are used to describe the progresses of the badminton shoes relate to exercise in some training aspects, which can be searched by CNKI and SCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…From the cognitive science perspective, colour can influence human cognition, perception and behaviour, which may in turn has great impact on motor performances [6,[51][52][53]. The earliest study investigating the color of badminton shoes [54] indicated that badminton shoes should concentrate on exciting colors (e.g. red) and material combinations, which could help to improve the wearer's sports performance perception.…”
Section: Discussionmentioning
confidence: 99%
“…From the cognitive science perspective, colour can influence human cognition, perception and behaviour, which may in turn has great impact on motor performances [6,[51][52][53]. The earliest study investigating the color of badminton shoes [54] indicated that badminton shoes should concentrate on exciting colors (e.g. red) and material combinations, which could help to improve the wearer's sports performance perception.…”
Section: Discussionmentioning
confidence: 99%
“…So, if a player in Glicko system has a very high RD and the 𝑅𝐷 𝑠𝑡𝑒𝑝 is low, in the first few matches, the player will always get a very high rating change because the RD is very high, unlike the Glicko-2, the RD drops dramatically when player's RD is very high, so the player will be tough for the constantly large change of rating. This phenomenon is very likely that in the badminton exercise [7]. And, when the player's RD lowered down, the magnification declines more, so the player will feel that the change rate of rating highly declined suddenly.…”
Section: Case Of the Player's Rd Is Highermentioning
confidence: 98%
“…Complementing the geographic examination, this paper dives into the person ventures of Kento Momota and Axelsen, whose competitive and exceptionally diverse directions in 2019 embody the competitive soul of the don [3]. The author will track their exhibitions within the competition through the focal point of insights, analyzing scores, matches, and key minutes that characterized their year.…”
Section: Introductionmentioning
confidence: 99%